Pengaruh Lingkungan Kerja dan Kompensasi terhadap Kinerja Karyawan dengan Mediasi Kepuasan Kerja pada Karyawan Generasi Milenial di Surabaya - Sabita Mawardah; Tjahjani Prawitowati (Universitas Batanghari Jambi, 2023)
This study aims to examine the influence of work environment and compensation on employee performance by mediating job satisfaction in millennial generation employees in Surabaya. The sample consisted of 116 millennial employees working in companies in surabaya, aged 24-40 years and had a minimum of one year of service. The sampling technique uses judgment sampling. Analysis using structural equating modeling (SEM) on partial least square (PLS) and data collection using a questionnaire in the form of google form. The results of this study indicate that the work environment has no effect on job satisfaction and employee performance. Effect of compensation on employee performance. Compensation has no effect on job satisfaction and employee performance, job satisfaction has a positive and significant effect on employee performance, job satisfaction is not proven as a mediation of the influence of the work environment on employee performance and the effect of compensation on employee performance. Theoretical and practical implications are also discussed as a follow-up to the research result discussion.